2011
DOI: 10.1105/tpc.111.089847
|View full text |Cite|
|
Sign up to set email alerts
|

Single Cystathionine β-Synthase Domain–Containing Proteins Modulate Development by Regulating the Thioredoxin System in Arabidopsis    

Abstract: Plant thioredoxins (Trxs) participate in two redox systems found in different cellular compartments: the NADP-Trx system (NTS) in the cytosol and mitochondria and the ferredoxin-Trx system (FTS) in the chloroplast, where they function as redox regulators by regulating the activity of various target enzymes. The identities of the master regulators that maintain cellular homeostasis and modulate timed development through redox regulating systems have remained completely unknown. Here, we show that proteins consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 80 publications
2
90
0
Order By: Relevance
“…Mutations in CBS domains impair the function of the associated enzymes (Kushwaha et al, 2009). Enzyme activation by CBS proteins occurs through binding to S-adenosylMet, AMP, or ATP, which changes the CBS pair domain structure and thereby activates the enzyme (Kushwaha et al, 2009;Yoo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in CBS domains impair the function of the associated enzymes (Kushwaha et al, 2009). Enzyme activation by CBS proteins occurs through binding to S-adenosylMet, AMP, or ATP, which changes the CBS pair domain structure and thereby activates the enzyme (Kushwaha et al, 2009;Yoo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, as we speculated above, MtCBS1 is involved in formation of the IT wall. Interestingly, in Arabidopsis it has been shown that a single soluble CBS domain-containing protein regulates cellular redox homeostasis by interacting with thioredoxin and thereby controls maturation of the cell wall (Yoo et al, 2011). Currently, it is thought that regulation of reactive oxygen species (ROS) in the IT is important to ensure an appropriate level of cross linking within the plant cell wall to maintain its integrity while allowing IT growth and bacterial infection (Santos et al, 2001;Brewin, 2004;Jamet et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Calvin cycle CP12 (Fig. 3), a small chloroplast protein increasingly recognized as master regulator of the Calvin cycle, complexes to downregulate GAPDH under oxidative conditions to form the binary complex A4-GAPDH/CP12, which strongly suppresses GAPDH activity (see GAPDH expression above; Wedel et al, 1997;Gontero and Maberly, 2012;Michelet et al, 2013;López-Calcagno et al, 2014) and is essential to the leaves' response to abiotic/oxidative stress (Yoo et al, 2011). The consistent up-regulation of universal stress protein and isoprene synthesis also agrees with the high abiotic stress conditions potentially produced by hydrocarbon contamination (Maqbool RNA biding proteins are emerging as regulators of plant responses to environmental stress (Ambrosone et al, 2012).…”
Section: Mapping Extracted Rna To Independently De Novo Assembled Tramentioning
confidence: 99%
“…Regions 15 and 47 also contain thioredoxin genes, and region 73 contains CYSTATHIONINE b-SYNTHASE DOMAIN-CONTAINING PROTEIN3 (CBSX3). CBSX3 is one of several CBSX proteins that regulate the thioredoxin system (Yoo et al, 2011). Investigation of these genes may reveal additional details of the connection of Pro metabolism to redox status.…”
Section: Gwas Identifies Genes Connecting Pro Accumulation To Cellulamentioning
confidence: 99%